Assessing Social Media Influencer Credibility And Its Impact On Consumer Purchase Intentions In Emerging Markets: A Case Study Of Ghana - Pessey, Melody Abena (UniMAC, 2025)
Social media influencer marketing has become a dominant promotional strategy in emerging digital economies, yet limited empirical evidence exists on how different dimensions of influencer credibility shape consumer purchase intentions within the Ghanaian context. This study examined the effect of social media influencer credibility on consumer purchase intentions in Ghana, with particular attention to the mediating roles of consumer trust and parasocial interaction, and the moderating role of perceived product-related risk. Grounded in Source Credibility Theory, the study adopted a quantitative, explanatory, cross-sectional survey design. Data were collected from 260 active social media users in Ghana who follow at least one influencer and have been exposed to influencer promotions. Structured questionnaires were administered online, and data were analyzed using descriptive statistics, Pearson correlation and multiple regression techniques. The findings revealed that perceived expertise, trustworthiness, authenticity/congruence and transparency significantly and positively influence consumer purchase intentions, while attractiveness was not a significant predictor when other credibility dimensions were controlled. Mediation analysis confirmed that both consumer trust and parasocial interaction partially mediate the relationship between influencer credibility and purchase intention. Moderation analysis further showed that perceived product-related risk strengthens the positive effect of credibility on purchase intention, indicating that credibility becomes more decisive under high-risk purchase conditions. The study concludes that cognitive and moral dimensions of credibility are more influential than physical appeal in shaping purchasing intentions in Ghana’s digital marketplace. The findings extend Source Credibility Theory by integrating relational and risk-based mechanisms and offer practical guidance for brands, influencers and regulators on building credible and ethical influencer marketing strategies. The study contributes context-specific empirical evidence to the growing influencer marketing literature in Africa.
MA Thesis
Keywords: Social media influencer; marketing; digital economies; consumer trust; Ghana